Sosialisasi Praktek Adzan Bagi Remaja Dalam Kegiatan Festival Anak Sholeh Di Desa Sekoci Kecamatan Besitang - Muhmmad Saleh; Ali Mukhlis; Zainur Lingga; Ariska Julianti; Rika Kumala; Siti Ayuni; Wafiqa Zahra (peduli riset dan pengabdian masyarakat, 2023)
The call to prayer, in addition to notifying that the time for prayer has arrived, and calling for congregational prayers, is also on the other hand to broadcast Islam in public. The pronunciation of the call to prayer contains many meanings that contain important meanings, including from the point of view of belief, such as the existence of the Almighty God who is One, there is no partner for Him, explaining that the Prophet Muhammad is the messenger of God. After we testify that there is no god but Allah and Muhammad is the messenger of Allah, we are then invited to achieve victory both in this world and in the hereafter. The call to prayer and iqomah are finally closed with the sentence of monotheism